Efektifitas Konseling Kelompok dalam Mengatasi Kecemasan Menghadapi Tes Kemampuan Akademik di SMAN 3 Lubuk Basung - Mira Eka Marsusi; Darimis (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
This study aims to examine the effectiveness of group counseling in alleviating students' anxiety related to the Academic Ability Test. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving six twelfth-grade students who participated in group counseling sessions based on Rational Emotive Behavior Therapy (REBT). The findings reveal a significant reduction in academic anxiety levels following the intervention. Group counseling was found to provide a reflective space, emotional support, and social learning that facilitated psychological recovery. These results contribute to the development of school-based guidance and counseling services and reinforce the theoretical effectiveness of REBT in group settings. The study recommends the integration of group counseling into regular school programs prior to academic examinations.